2010
DOI: 10.1111/j.1365-2567.2010.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A is required to suppress invasion of Salmonella enterica serovar Typhimurium to enteric mucosa

Abstract: Summary Salmonella enterica serovar Typhimurium (S. typhimurium) causes a localized enteric infection and its elimination is dependent on a T helper type 1 immune response. However, the mechanism of the protective immune response against the pathogen in gut‐associated lymphoid tissue (GALT) at an early stage of the infection is not yet clarified. Here, we show that interleukin‐17A (IL‐17A) was constitutively expressed in GALT; it was also detected on crypt and epithelial cells of the small intestine. Neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…IL-22 exerts its protective effects by inducing epithelial cells to produce antibacterial molecules (37). Recently, Th17 responses have been demonstrated to have protective roles against Salmonella and Citrobacter infections in mice (29,30). To date, only limited data exist regarding Th17 responses and Campylobacter infection.…”
Section: Fig 4 Il-17 Expression Is Reduced In Small Intestinal Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-22 exerts its protective effects by inducing epithelial cells to produce antibacterial molecules (37). Recently, Th17 responses have been demonstrated to have protective roles against Salmonella and Citrobacter infections in mice (29,30). To date, only limited data exist regarding Th17 responses and Campylobacter infection.…”
Section: Fig 4 Il-17 Expression Is Reduced In Small Intestinal Cd4mentioning
confidence: 99%
“…These models can be exploited to evaluate innate or adaptive Th17 responses. Whereas iTh17 responses can be induced relatively quickly by cytokine signals (29,30), adaptive Th17 responses occur later (days to weeks) (34) and are antigenspecific responses. In our present study, the Th17 responses likely represented an adaptive immune response, since Jackson Laboratory mice were used.…”
Section: Fig 4 Il-17 Expression Is Reduced In Small Intestinal Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was reported that mice lacking the IL-17 receptor were defective in the long-term control of M. tuberculosis infection (156). On the other hand, M. tuberculosis and Salmonella infections are controlled normally in IL-23-deficient mice, in which Th17 generation does not occur (157,158), and neutralization of IL-17 had no effect on the control of L. major infection (159). Furthermore, people with mutations that affect the expression of IL-17 or IL-17 receptor are susceptible to Candida and Staphylococcus aureus skin infections (160) but do not appear to be susceptible to the phagosomal pathogens that afflict people lacking CD4 ϩ T cells or IL-12 receptor (27,28,161).…”
Section: Srivastava and Ernst Recently Shed Light On How The Interactmentioning
confidence: 99%
“…The early loss of the enterocyte-proliferative and antimicrobial peptide-inducing cytokines produced by T h 17 cells impairs the integrity of the gut mucosal barrier, driving microbial translocation and chronic immune activation-key determinants of disease progression to AIDS (25,26).…”
mentioning
confidence: 99%